E-PAYMENT: INOVASI LAYANAN PENGHIMPUNAN DAN REDISTRIBUSI WAKAF UANG BERBASIS ONLINE DALAM PERCEPATAN PEMBANGUNAN EKONOMI INDONESIA - Izra Berakon; Agus Muhammad Irsad (AL-QARDH, 2017)
Indonesia as a majorMuslim population country, has a large potential of cash waqf. Indonesian Waqf Board (BWI) predicted the potential of cash waqf in Indonesia is Rp 20 trillion, but had not followed by the effective collection method, so that potential has not been able to develop optimally. On the other hand, technology grown rapidly, followed by the numberof internet users in Indonesia. Based on the data of  the Association of Internet Service Providers Indonesia (APJII) shows that internet users in Indonesia by aged 20 years and plus, reached 119.2 million inhabitants. It allows the integration of  the effective system of collectingwaqf property. One of the effective collecting efforts done by the government is to establish a waqfbank which role as nadzir beside a liason between wakif with the waqf management institutions. The main duty ofwaqf management institution here is as nadzir who will manage cash waqfproductively and fostering the communityso as toempower the economy. However, the current establishment of waqf bank is still in the process of finalization, so there is no core principle in collecting waqf. Therefore, the purpose of this research is to offer an electronic application of collecting and redistributing cash waqf by the internet networking and the development of the digital era. It concept called e-payment.It choosen an e-payment as the concept, which wakif must fill the balance of waqf bank account from commercial bank accounts owned by wakif. Then wakif choose waqfallocation with options that have been provided by waqfbank.The research method usedis descriptive analysis and conjoint analysis. The final implication by the innovation of the e-payment application is that the existing ease of waqfcollection is expected to be effective and reach many people and able to increase the economy of Indonesian society.